2018
DOI: 10.1186/s13000-018-0690-3
|View full text |Cite
|
Sign up to set email alerts
|

Analytic validity of DecisionDx-Melanoma, a gene expression profile test for determining metastatic risk in melanoma patients

Abstract: BackgroundThe DecisionDx-Melanoma test provides prognostic information for patients with cutaneous melanoma (CM). Using formalin-fixed paraffin-embedded primary tumor tissue, the RT-PCR-based test classifies patients into a low- (Class 1) or high-risk (Class 2) category for recurrence based on expression of 31 genes. The current study was designed to assess the analytical validity of this test.MethodsInter-assay, inter-instrument, and inter-operator studies were performed to evaluate reliability of the 31-gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 20 publications
2
36
0
Order By: Relevance
“…The formalin-fixed paraffin-embedded primary cutaneous melanoma tissue was analysed with the 31-GEP test (DecisionDx-Melanoma, Castle Biosciences, Inc). 15,25 Moreover, the RT-PCR-based test classifies patients into a low-risk (Class 1) or high-risk (Class 2) category for recurrence, as previously reported and validated. 15 Disease-free survival (DFS) was defined as the period of time in months from the date of diagnosis to the date of relapse.…”
Section: Methodsmentioning
confidence: 91%
See 2 more Smart Citations
“…The formalin-fixed paraffin-embedded primary cutaneous melanoma tissue was analysed with the 31-GEP test (DecisionDx-Melanoma, Castle Biosciences, Inc). 15,25 Moreover, the RT-PCR-based test classifies patients into a low-risk (Class 1) or high-risk (Class 2) category for recurrence, as previously reported and validated. 15 Disease-free survival (DFS) was defined as the period of time in months from the date of diagnosis to the date of relapse.…”
Section: Methodsmentioning
confidence: 91%
“…P-values <0.05 were considered significant. Statistical analyses were performed using SPSS v. 25.0 (IBM Corp., Armonk, NY, USA), and Cox regression analysis was performed using R studio (R Studio Team (2015). RStudio: Integrated Development for R. RStudio, Inc., Boston, MA, USA).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genes included in the 31‐GEP were distilled from a comparative review of multimarker studies performed between 2000 and 2011, from which over 150 genes associated with recurrence were identified . The test includes three control genes and 28 prognostic genes that have been validated in three multicenter retrospective cohorts, two prospective studies, and an analytic analysis that reported robust reproducibility of the test (98% technical success rate in 8244 clinically tested specimens) . Unlike the tests described above, the 31‐GEP uses radial basis machine (RBM) pattern recognition modeling to compare the GEP of a test sample to a training set containing 164 melanoma tumors with known outcomes.…”
Section: Biomarkersmentioning
confidence: 99%
“…4,5 Its prognostic value is likely to be associated with its surrogacy for tumor size, which correlates with risk of metastasis, as exemplified by breast cancer. 6 At present, active pursuit of molecular prognostic biomarkers such as the DecisionDx-Melanoma test (Castle Biosciences, Inc) 7,8 have the advantage of a rational basis founded on tumor biology, but these tests can be expensive and require specialist equipment or laborious protocols. Therefore, we focused on microscopic biomarkers requiring no more than the hematoxylin-eosin (H&E)-stained sections used for diagnosis.…”
mentioning
confidence: 99%